FENOMENA FLYPAPER EFFECT: STIMULAN ATAU KEMUNDURAN DESENTRALISASI FISKAL? - Bolang, Rikhard Titing Christopher (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2024)
This research aims to analyze the flypaper effect phenomenon in East Nusa Tenggara (NTT) Province and its impact on the implementation of fiscal decentralization in East Nusa Tenggara (NTT) Province. Using the panel data regression analysis method based on the choice of models carried out including Random Effect Model, Fixed Effect Model, and Common Effect Model which concluded that the best model used in this study was the Fixed Effect Model through the Chow Test and Hauman Test. The results of the test using the Fixed Effect Model explain that statistically the Balancing Fund variable has a significant effect on regional spending but does not apply to the PAD variable. In terms of the existence of the flypaper effect in the Regency/City government of East Nusa Tenggara Province (NTT), it is concluded that there is a flypaper effect phenomenon which is seen based on the coefficient value of the Balancing Fund variable which is greater than the coefficient value of PAD. So based on this analysis, it is concluded that there is a decline in fiscal decentralization if the use of the Balancing Fund, one of which is the General Allocation Fund (DAU), is still used as a source of financing for regional spending by the Regional Government.